DISCOURS LITERATOURNO-FOLCLORISTIC OF GEORGE LYPA - Cachcan, V. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Payment of George Lypa in the theory of state building, his poetic and prosaic reserve, epistolary inheritance is analyzed.